Forecasting User Responsiveness to Sponsored Advertisement over Social Media through the TAM - Gridwichai, Piched; Piromkam, Bunjob; Kwanmuangvanich, Parinya; Phonsri, Nuttavut (International Journal of Psychosocial Rehabilitation, 2020)
Sponsored advertisement has produced effective marketing returns for Facebook in last few years. Since sponsored advertisement is generated over an interactional platform that would be observed as intrusive to individual’s privacy, the enhancement of this advertisement platform has significant implications for customers, and ads equivalent. Although limited literature is available on user responsiveness to sponsored advertisement, this study evaluates the influence of individual assumption of confidentiality venture, curiosity issues and services of sponsored advertisement over customer conducts and buying intention. Estimating a paradigm proposed via TAM (Technology Acceptance Model), this study finds that confidentiality and curiosity issues are both authentic precedence variables to assumed usefulness instead of assumed feasibility of utilization of sponsored ads, only confidentiality issues possess influence over items buying intentions. The hypothetical statements association among assumed usefulness, feasibility of utilization, conducts and buying intentions were also verified.